Exchange current densities at electrochemical phase formation from molten salts - Isaev V.A.; Grishenkova O.V. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The processes of nucleation, growth and phase formation during electrodeposition from molten salts have been studied. Theoretical methods for the determination of nucleation and growth parameters, particularly exchange current densities at the melt/new phase cluster interface, are considered.